2022
DOI: 10.21203/rs.3.rs-1306439/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

M6A-Mediated Upregulation of CircMDK Promotes Tumorigenesis and Acts as a Nanotherapeutic Target in Hepatocellular Carcinoma

Abstract: Background: Emerging evidences suggest the critical role of circular RNAs (circRNAs) in disease development especially in various cancers. However, the oncogenic role of circRNAs in hepatocellular carcinoma (HCC) is still largely unknown.Methods: RNA sequencing was performed to identify significantly upregulated circRNAs in paired HCC and non-tumor tissues. CCK-8 assay, colony formation, transwell, and xenograft mouse models were used to investigate the role of circRNAs in HCC proliferation and metastasis. Sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…To name only a few, Jie et al 27 have reported thathsa_ circ_0102004 promoted prostate cancer cell proliferation, Zheng et al 28 have reported that hsa_circ_0023028 contributed to the progression of laryngeal squamous cell carcinoma. Du et al 29 have also reported that hsa_circ_0095868 upregulated by M6A promotes the tumorigenesis of hepatocellular carcinoma. Our study focused on the role of circPPP1R12A in NSCLC.…”
Section: Discussionmentioning
confidence: 95%
“…To name only a few, Jie et al 27 have reported thathsa_ circ_0102004 promoted prostate cancer cell proliferation, Zheng et al 28 have reported that hsa_circ_0023028 contributed to the progression of laryngeal squamous cell carcinoma. Du et al 29 have also reported that hsa_circ_0095868 upregulated by M6A promotes the tumorigenesis of hepatocellular carcinoma. Our study focused on the role of circPPP1R12A in NSCLC.…”
Section: Discussionmentioning
confidence: 95%
“…IGF2BP1 recognizes the m6A modification site in circMDK to increase the stability of its transcripts. circMDK sponges miR-346, and miR-874-3p upregulates autophagy-related 16-like 1 (ATG16L1), thereby activating the PI3K/AKT/mTOR signaling pathway and promoting HCC cell proliferation, migration and invasion 134 . METTL3 and IGF2BP1 act together to increase the stability of LncAROD through m6A modification.…”
Section: Igf2bp1mentioning
confidence: 99%
“…Tumor growth was significantly suppressed by in vivo-optimized RNA interference (RNAi) inhibition of LINRIS 156 . PAEs to assist in the transport of circMDK siRNA (PAE-siRNA) were demonstrated to be effective in inhibiting tumor progression without causing significant adverse effects in four HCC models, including a subcutaneous model, orthotopic model, lung metastasis model and PDX model 134 . These studies suggest that targeting RNA effector molecules for clinical treatment is a promising research direction.…”
Section: The Clinical Potential Of Ncrnas and M6a Modifiersmentioning
confidence: 99%
“…CircMDK is novel oncogenic circRNA in hepatocellular carcinoma (HCC) with significantly increased expression in tumors. CircMDK promotes HCC progression via the miR‐346/miR‐874‐3p‐ATG16L1 axis and may be a therapeutic target for HCC [33]. M 6 A‐modified circMAP3K4 encodes a novel peptide, circMAP3K4‐455 aa, which prevents apoptosis in HCC [34].…”
Section: Circrnas As Biomarkers Of Cancermentioning
confidence: 99%